Building stone decay : from diagnosis to conservation - Přykryl, R.; Smith, Bernard J. (Geological Society special publication, 2007)
Stone buildings and monuments form the cultural centres of many of the world's urban areas. Frequently these areas are prone to high levels of atmospheric pollution that promote a variety of aggressive stone decay processes. Because of this, stone decay is now widely recognised as a severe threat to much of our cultural heritage. An interdisciplinary approach between geologists, environmental scientists, chemists, material scientists, civil engineers, restorers and architects aims to strengthen the knowledge base dealing with the causes, consequences, prevention and solution of stone decay problems.